USING POWTOON TO IMPROVE STUDENTS' LISTENING SKILLS: A SYSTEMATIC LITERATURE REVIEW - Mardiatun Nissa; Frida Dini Chaerunnisa; Teti Elawati; Naf an Tarihoran (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
The development of digital technology has brought significant changes to English language learning, particularly in the development of listening skills, which are often considered difficult by EFL learners. Powtoon, as an animation-based audio-visual medium, is relevant because it provides visual support that helps students understand spoken input more clearly. This study aims to systematically review studies on the use of Powtoon to improve students' listening skills. The method used is a Systematic Literature Review (SLR) following the PRISMA guidelines, covering the processes of identification, screening, eligibility assessment, and inclusion of articles published between 2020 and 2025 from Mendeley, ERIC, PubMed and Google Scholar. A total of five articles that met the criteria were analyzed in depth. The study's results show that Powtoon generally increases students' attention, motivation, and engagement during listening activities. The majority of studies reported a significant increase in listening comprehension, mainly because contextual visualization reduced students' cognitive load. However, one study found that the increase was not significant, suggesting that Powtoon's effectiveness is influenced by the learning design and its application. Powtoon is a potential medium for supporting listening and learning and has important implications for teachers in integrating multimedia to improve student comprehension